Intramuscular allopregnanolone and ganaxolone in a mouse model of treatment‐resistant status epilepticus. (17th February 2018) - Zolkowska, Dorota; Wu, Chun‐Yi; Rogawski, Michael A.
Summary: Allopregnanolone (5α‐pregnan‐3α‐ol‐20‐one) and its synthetic 3β‐methyl analog, ganaxolone, are positive allosteric modulators of synaptic and extrasynaptic γ‐aminobutyric acid (GABA)A receptors that exhibit antiseizure activity in diverse animal seizure models, including models of status epilepticus (SE). The 2 neuroactive steroids are being investigated as treatments for SE, including as a treatment for SE induced by chemical threat agents. Intramuscular injection is the preferred route of administration in the prehospital treatment of SE. The objective of this study was to assess the efficacy of intramuscular allopregnanolone and ganaxolone in the treatment of SE induced by the chemical threat agent tetramethylenedisulfotetramine (TETS). The test agents were administered 40 minutes after the onset of SE when mice are refractory to treatment. Allopregnanolone and ganaxolone (each at 3 mg/kg) terminated SE in, respectively, 92% and 75% of animals, and prevented mortality in 85% and 50% of animals; the mean times to termination of behavioral seizures were, respectively, 172 ± 16 and 447 ± 52 seconds. In a separate series of experiments, mice were dosed with the neuroactive steroids by intramuscular injection, and plasma and brain levels were sampled at various time points following injection to estimate pharmacokinetic parameters. Plasma C max (maximum concentration) values for allopregnanolone and ganaxolone were 645 and 550 ng/mL, respectively. Brain exposure of both steroids was approximately 3‐fold the plasma exposure. Two‐compartment pharmacokinetic analysis revealed that the central compartment V d (volume of distribution), CL (clearance), t ½ (terminal half‐life), and F (intramuscular bioavailability) values for allopregnanolone and ganaxolone were, respectively, 4.95 L/kg 12.88 L/kg/h, 16 minutes, 97%, and 5.07 L/kg, 8.35 L/kg/h, 25 minutes, 95%. Allopregnanolone and ganaxolone are effective in the treatment of TETS‐induced SE when administered by the intramuscular route. Allopregnanolone is more rapidly acting and modestly more effective, possibly because it has greater potency on GABAA receptors.